DEVELOPMENT OF THE CONE PRESSUREMETER - Houlsby, G; Nutt, N (1993)
Methods of interpretation of the cone pressuremeter in clay and in sand are discussed. A method of analysis for the test in clay had previously been compared with results in stiff overconsolidated clay, and is compared here with results in soft clay at Bothkennar. Both shear strength and shear modulus can be measured successfully, and a discussion is presented of comparisons of shear modulus measured by different techniques. In sand interpretation methods are based on correlations determined from calibration chamber tests. The correlations can be used to estimate horizontal stress and relative density, and unload-reload loops can be used to determine stiffness. -from Authors